MENINGKATKAN KEMAMPUAN MENULIS JENIS TULISAN BALOK MELALUI MEDIA WRITING FRAME PADA ANAK LOW VISION KELAS II DI SLB FAN REDHA PADANG - Aidil Fitriyaldi, Asep Ahmad Sopandi, Elsa Efrina (Universitas Negeri Padang, 2013)
The research was background by the problems that researcher found in ability of writing child with Low Vision Needs in class II junior high special school Fan Redha Padang. The researchers want to prove that the use of media writing Frame can improve the ability to write of child with Low Vision Needs. This research using Single Subject Research approach, the A-B design and data analysis techniques using visual analysis chart. Results of this study indicate that the media Writing Frame has improve the ability to write child with Low Vision Needs in class II junior high special school Fan Redha Padang.